Analysis of relevant factors in patients with oral and pharyngeal cancers - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Moreno, Amália [UNESP]; Ribeiro, Paula do Prado [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Santos, Emerson Gomes dos (My University, 2013)
This study presented an epidemiological data of 177 medical records of patients affected by oral and pharyngeal cancers with prosthesis indication. The gender, age, sun exposure, disease diagnosis, cancer anatomic site, radiation treatment and type of prosthesis, death from oral and pharyngeal cancers were collected. Data were analyzed by summary measures and logistic regression analysis. The mean age of the patients was 62.7 years, and 46.8％ died between 52 and 62 years old. Most of the patients were male (74％), and 42％ died among them. Squamous cell carcinoma was the most prevalent cancer (75.1％) and 42.1％ of these patients died. The age, gender, diagnosis and the interaction of these factors exhibited strong association with the patients’ death (P<.05, Chi-square test). The multivariate odds ratios (OR) of the death were 0.40 for women and 0.39 for other pathologies versus male and squamous cell carcinoma, respectively. It was concluded that age, gender and diagnosis of cancer had significant effect on patients’ death.